Life‐history theory provides a framework for detecting resource limitation: a test of the Nutritional Buffer Hypothesis. Issue 4 (8th March 2021) - Jesmer, Brett R.; Kauffman, Matthew J.; Courtemanch, Alyson B.; Kilpatrick, Steve; Thomas, Timothy; Yost, Jeff; Monteith, Kevin L.; Goheen, Jacob R.
Abstract: For ungulates and other long‐lived species, life‐history theory predicts that nutritional reserves are allocated to reproduction in a state‐dependent manner because survival is highly conserved. Further, as per capita food abundance and nutritional reserves decline (i.e., density dependence intensifies), reproduction and recruitment become increasingly sensitive to weather. Thus, the degree to which weather influences vital rates should be associated with proximity to nutritional carrying capacity—a notion that we refer to as the Nutritional Buffer Hypothesis. We tested the Nutritional Buffer Hypothesis using six moose ( Alces alces ) populations that varied in calf recruitment (33–69 calves/100 cows). We predicted that populations with high calf recruitment were nutritionally buffered against the effects of unfavorable weather, and thus were below nutritional carrying capacity. We applied a suite of tools to quantify habitat and nutritional condition of each population and found that increased browse condition, forage quality, and body fat were associated with increased pregnancy and calf recruitment, thereby providing multiple lines of evidence that declines in calf recruitment were underpinned by resource limitation. From 2001 to 2015, recruitment was more sensitive to interannual variation in weather (e.g., winter severity, drought) and plant phenology (e.g., duration of spring) for populations with reduced browse condition, forage quality, and body fat, suggesting these populations lacked the nutritional reserves necessary to buffer demographic performance against the effects of unfavorable weather. Further, average within‐population calf recruitment was determined by regional climatic variation, suggesting that the pattern of reduced recruitment near the southern range boundary of moose stems from an interaction between climate and resource limitation. When coupled with information on habitat, nutrition, weather, and climate, life‐history theory provides a framework to estimate nutritional limitation, proximity to nutritional carrying capacity, and impacts of climate change for ungulates.